Acute appendicitis in pregnancy: literature review - Franca Neto,Antônio Henriques de (2015)
Introduction: suspected appendicitis is the most common indication for surgery in non-obstetric conditions during pregnancy and occurs in about one in 500 to one in 635 pregnancies per year. This occurs more often in the second trimester of pregnancy. Acute appendicitis is the most common general surgical problem encountered during pregnancy. Methods: a literature review on research of scientific articles, under the terms “acute appendicitis” and “pregnancy”, in PubMed, Lilacs/SciELO, Scopus, Cochrane Library and Uptodate databases. Results: the clinical manifestations of appendicitis are similar to non-pregnant women, however, without a classic presentation, which often occurs, diagnosis is difficult and must be supported by imaging. Discussion: clinical diagnosis should be strongly suspected in pregnant women with classic findings such as abdominal pain that migrates to the right lower quadrant. The main purpose of imaging is to reduce delays in surgical intervention due to diagnostic uncertainty. A secondary objective is to reduce, but not eliminate, the negative appendectomy rate. Differential diagnosis of suspected acute appendicitis usually includes pathologies considered in non-pregnant people. Conclusion: the imaging study of choice is ultrasound, MRI may be used when the former is not conclusive and, as a last resort, a CT scan can be performed. The treatment remains appendectomy by laparotomy, since the feasibility of video- assisted surgery in these cases remains controversial.